Student Leadership Character In Educational Research: A Bibliometric Analysis Of The Last Two Decades - Hapsari, Maulani Mega; Martono, Trisno; Wardani, Dewi Kusuma; Noviani, Leny (Jurnal Pendidikan Karakter, 2024)
Modern education increasingly recognizes student leadership as an important channel for developing a sense of responsibility, resilience, and cooperation. Yet, despite its increasing significance, there is a lack of an overall analysis of research on student leadership. This study presents a bibliometric review of research published from 2003 through 2024 on main trends, publication patterns, and emergent themes. Using the PRISMA framework, relevant articles were retrieved from Scopus, targeting English research articles and reviews. Of the 548 identified documents, 348 were analyzed. The results highlight the growing significance of student leadership, especially in healthcare, social sciences, and engineering, with U.S.-based research dominating the field, indicating global research imbalances. Based on the co-occurrence analysis, the common themes identified are Leadership within healthcare education, Curriculum development, Gender dynamics, and the student-centered approach. These themes reflect the key areas of focus in current research on student leadership. These findings assist educators, policymakers, and researchers in guiding the enhancement of development in student leadership.Keywords: bibliometrics, education, leadership character, student.